نبی کریم ﷺبطورسیاست دان؛ ایک تجزیاتی مطالعہ: An analytical study of The Holy Prophet Muhammad’sﷺ Political life - razzaq, Dr.Tayyaba; Akbar, Dr. Hafiz Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
Islam gave to mankind an ideal code of human rights fourteen centuries ago. These rights aim at conferring honor and dignity on mankind and eliminating exploitation, oppression and injustice. Islam is a social religion, not in the sense that it is through society alone that religion breathes its sacred spirit in the individuals, but in the sense that it aims at inculcating God-consciousness both in individual and society. The Holy Prophet was holding so much important responsibility as the Head of the State; confer at every occasion that he, as the great benefactor, bravely performed legal and political heroic deeds which are examples of their own in the world of deeds. This paper aims to analyze the administration during the time of the Holy Prophet ﷺ and illustrate its importance in today’s times. The Holy Prophet ﷺ had introduced basic norms of Public Administration and practically presented an administrative model. The Prophet Muhammadﷺ acted upon the shariah rules, set many examples and developed devices to resolve disputes by peaceful methods. He ﷺ commanded his nation with honor, justice, equality, peace, and respect to humanity. Keywords; Holy Prophet ﷺ, Political life, State, peace, justice, Humanity, dignity of mankind.